Sistematización de Fichas Médicas Ocupacionales y Test Psicológicos - Castro Valarezo, Yannela Mishelle (2023)
The lack of a system to digitalize the medical information of patients at the Subdirection of Occupational Safety and Health of the National University of Loja has allowed to propose this Degree Project with the objective of designing a software for the systematization of Occupational Medical Records of the employees who work in the institution. The first phase is to analyze the current situation of information management within the Occupational Safety and Health Subdirectorate, the interview technique, and with the results obtained we were able to specify the requirements for the construction of the module. In the second phase, to develop a software that facilitates the systematization of occupational medical records, the hybrid ScrumXP methodology was used, consisting of three stages which are: Planning-Definition, Development, and Delivery and Maintenance, which are fulfilled in each iteration defined within the project, likewise use was made of Kruchten's 4+1 architecture views model, designing the different UML diagrams that represent each view that, together with the development technologies required by the Information Technology Department, allowed the correct coding of the software. Finally, in the third phase to evaluate the operation of the software, a test plan was defined in which the set of unit tests and acceptance tests that were executed within the module were established, with the support of DTI, and with the results of the tests it was verified that the development of the module was carried out successfully and the functionalities implemented satisfy the requirements initially established by those involved who will make use of the software solution, which implies that the process of medical information management within the Occupational Safety and Health Subdirectorate has been automated. Keywords: Digitalization, Medical Records, Occupational Health, Systematization, ScrumXP Hybrid Methodology.